Entropy-based Constant and Variable Weight Determination for Decision Makers in Multi-Criteria Group Decision Making - Tuncay Gürbüz; Sevra Çiçekli (Havacılık ve Uzay Teknolojileri Dergisi, 2024)
Properly assigning weights to decision makers in a group decision making environment is one of the essential processes of utmost importance as it can have a direct effect on the final outcome. This paper, basing on the entropy method, proposes a correct and efficient way to objectively assign weights to decision makers in a multi-criteria group decision making environment. Two approaches namely, constant and variable weighting, have been put forward whilst providing necessary proofs and numerical examples in order to show one of the existing ways in literature is erroneous as it is not resulting in weights that reflects entropy method’s basic intuition.